Case study of the fit of literary form and the theosophic meaning in the Fayyad Lahiji's Divan - Akram aghili; Sayyed Morteza Mir Hashemi (حکمت اسرا)
Fayyad Lahidji, a philosopher and mystic of the Safavid era, is one of the poets who wrote poetry in Hindi poetry. These two intellectual and artistic springs, in conjunction with each other, have created a form of poetry that is unique in its own right. In the article, we will show that his poems are technically acceptable to the aesthetic criteria and are in terms of content according to the original verbal, moral and mystical views of Islam. A review of these two companion streams will show how it affects each other and has shaped the form and content of his poems. In order to illustrate this interplay, in this article we compare the aspects of the poetic and extrinsic music of his poems with the content of his ghazals and his anecdotes.